Răspuns :
b)
[tex] \frac{1}{2} \times ( \frac{1}{2} \times ( \frac{1}{2} x - 1) - 1) - 1) - 1 = 0 \\ \frac{1}{2} \times ( \frac{1}{2} \times ( \frac{1}{4} x - \frac{1}{2} - 1) - 1) - 1 = 0 \\ \frac{1}{2} \times ( \frac{1}{2} \times ( \frac{1}{4} x - \frac{3}{2} ) - 1 ) - 1 = 0 \\ \frac{1}{2} \times ( \frac{1}{8} x - \frac{3}{4} - 1) - 1 = 0 \\ \frac{1}{2} \times ( \frac{1}{8} x - \frac{7}{4} ) - 1 = 0 \\ \frac{1}{16} x - \frac{7}{8} - 1 = 0 \\ \frac{1}{16} x - \frac{15}{8} = 0 \\ x - 30 = 0 \\ x = 30[/tex]
c)
[tex] \frac{5x - 7}{2} - \frac{2x + 7}{3} = 3x - 14 \\ 3 \times (5x - 7) - 2 \times (2x + 7) = 18x - 84 \\ 15x - 21 - 4x - 14 = 18x - 84 \\ 11x - 35 = 18x - 84 \\ 11x - 18x = - 84 + 35 \\ - 7x = - 49 \\ - x = - 7 \\ x = 7[/tex]